Comparative therapeutic use of Risedronate and Calcarea phosphorica - Allopathy versus homeopathy - In bone repair in castrated rats - Werkman, Cristina [UNESP]; Senra, Giselle Segnini [UNESP]; da Rocha, Rosilene Fernandes [UNESP]; Brandão, Adriana Aigotti Haberbeck [UNESP] (FapUNIFESP (SciELO), 2006)
Osteoporosis, a disease characterized by progressive bone loss, has been the target of several studies in the past few years. It results in a much higher risk for fractures and might cause slower bone lesion healing. The aim of this work was to study the effects of Risedronate (allopathic medicine) and Calcarea phosphorica 6CH (homeopathic medicine) on the repair of bone lesions in male rats with osteoporosis induced by castration. Eighty-four three-month-old rats were used divided into four groups of twenty-one animals each. Three groups where castrated and one group was submitted to Sham surgery. One month later, cortical lesions were made in all animals' tibiae and, after one day, the different experimental treatments began according to the following groups: CR - castrated/Risedronate (1 mg/kg/day); CCp - castrated/ Calcarea phosphorica 6CH (3 drops/day); CP - castrated/placebo and SP - Sham/placebo. The animals were sacrificed at seven, fourteen and twenty-eight days after the beginning of the treatments and had their tibiae removed. Digital radiographs of the tibiae were taken and analyzed in order to evaluate the optical density of the defect area. Then, they were decalcified and processed for histological and histomorphometrical analysis. The data were submitted to ANOVA, and to the Tukey and Dunnett tests (5%). The allopathic and homeopathic treatments led to different bone formation as regards remodeling and maturation aspects. Further research is necessary to access the resistance and quality of the newly formed bone.
Keywords: Allopathy; Calcarea phosphorica; Fracture healing; Homeopathy; bone density conservation agent; calcium phosphate; drug derivative; etidronic acid; plant medicinal product; risedronic acid; analysis of variance; animal; bone density; bone remodeling; disease model; drug effect; male; orchiectomy; osteoporosis; pathology; phytotherapy; rat; Analysis of Variance; Animals; Bone Density; Bone Density Conservation Agents; Bone Remodeling; Calcium Phosphates; Disease Models, Animal; Etidronic Acid; Male; Orchiectomy; Osteoporosis; Phytotherapy; Plant Preparations; Rats